Secure resource allocation in hybrid energy-harvesting relay and full-duplex receiver - Wei WANG; Xinrui LI; Liuguo YIN; Guoan ZHANG; Shibing ZHANG (Tongxin xuebao)
Taking into account the wireless physical layer security in energy-constrained relaying systems,a secure resource allocation scheme was proposed under simultaneous wireless information and power transfer (SWIPT) protocol.The utility optimization problem was considered aiming to maximize the secrecy rate by jointly optimizing the power splitting (PS) ratio and the transmit powers under the constraint of the transmit powers of the nodes and the harvested energy of the relay.The objective problem,which is non-convex,was decoupled into two subproblems.One was to optimize the PS ratio,another was to optimize the transmit powers.The optimal solution of the subproblems can be obtained in the closed-form.Then,the suboptimal solution is obtained with the proposed convergent iterative algorithm.Simulation results show the effects of artificial noise signal,residual self-interference signal,transmit power of nodes,amplification factor of relay and other factors on the security performance.Compared with the traditional gradient descent algorithm,the proposed algorithm can reduce more than 80% of the computational load,while the algorithm has the slightly better performance.